Combined Synchrotron X _ ray and Neutron Powder Diffraction Studies of Ba2InSbO6 Ordered Double Perovskite - Shaheen, R.; Bashir, J.; Khan, M. N.; Shahzad, K. (The Nucleus, 2014)
The crystal structure of Ba2InSbO6, prepared via solid state reaction, has been investigated by powder neutron and Synchrotron Xray, diffraction techniques. From the detailed analysis of the diffraction patterns, it was shown that the crystal structure can be best described by the high-symmetry cubic doubled perovskite cell, space group , with cell parameters a = 8.2639(1) Ã…. The structure was found to be stable down to 100K making it a suitable candidate for growing thin films of high temperature superconductors.